Controversies and Perspectives in the Current Management of Patients with Locally Advanced Rectal Cancer—A Systematic Review - Roxana Elena Stefan; Rodica Daniela Birla; Mircea Gheorghe; Daniela Elena Dinu; Petre Angel Hoara; Diana Ciuc; Valeriu-Gabi Dinca; Silviu Constantinoiu (Life)
Traditionally, the therapeutic approach to rectal cancer has involved neoadjuvant chemoradiotherapy followed by surgical resection, and, in some cases, adjuvant chemotherapy. This study aims to present current advances and ongoing controversies in the management of patients with locally advanced rectal cancer (LARC), with a particular focus on clarifying the role of total neoadjuvant therapy (TNT) in contemporary treatment strategies. Methods: We conducted a systematic literature review in Medline/PubMed using various keyword combinations, including “rectal cancer/neoplasia” and“therapy” or “neoadjuvant therapy” or “TNT”, and included articles published between 2015 and 2025. Results: The association of neoadjuvant radiochemotherapy with preoperative systemic chemotherapy has led to the current concept of total neoadjuvant therapy. The advantages of preoperative chemotherapy include better patient compliance, a decrease in the rate of local recurrence and distant metastases via the early destruction of infra-clinical micrometastases, and higher rates of pathological complete response. All of these have led to the inclusion of this strategy in treatment guidelines for patients with locally advanced rectal cancer. Conclusions: However, the selection of patients with advanced rectal tumors for optimal therapy requires comprehensive imaging assessments, molecular and genetic testing, and a multidisciplinary team to determine the most appropriate total neoadjuvant therapy approach.